Pregnancy duration and breast cancer risk - Anders Husby (Nature Portfolio, 2018)
It is known that full-term pregnancies can reduce a woman’s breast cancer risk. Here, the authors interrogate data from 2.3 million Danish women, showing that this protective effect arises at precisely the 34th week of the pregnancy, and replicated this finding in 1.6 million women from Norway.